The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16152728
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Concern and Eating Disorder Symptoms Among Elite Icelandic Athletes

Abstract: The aim of this study was to analyse body image concerns and symptoms of eating disorders in elite Icelandic athletes according to their sex, and sport practiced. The participants were 755 athletes (24.8 ± 3.5 years in age) who compete at the highest possible level in Iceland. Representing 20 different sports, they were divided into five sports groups. Three questionnaires were used: the Body Shape Questionnaire to assess body image concerns; the Bulimia Test-Revised to assess the main symptoms of bulimia; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 50 publications
3
41
0
1
Order By: Relevance
“…Clinical-level EDs affect women at higher rates than men [ 14 , 15 ]. Eating disorders are particularly common in female adolescents and young adults (90% of cases occur in people under the age of 25) and seem to be more prevalent among athletes than in the general population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical-level EDs affect women at higher rates than men [ 14 , 15 ]. Eating disorders are particularly common in female adolescents and young adults (90% of cases occur in people under the age of 25) and seem to be more prevalent among athletes than in the general population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…BIC is one's wrong perception, feelings and thoughts of appearance and body which leads to significant distress and/or impairment,[ 29 ] depression and anxiety,[ 14 ] lower quality of life,[ 15 ] weight concerns,[ 16 ] and eating disorders. [ 8 ] So far, various studies have been conducted to determine the prevalence of BIC in adolescents. Its prevalence has been reported differently in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Body image is defined as a person's perception, feelings and thoughts about his/her body, incorporating body size estimation, the evaluation of body attractiveness, and various emotions associated with body shape and size;”[ 3 ] therefore, it can said that body image concern (BIC) is a multi-dimensional construct encompassing how we perceive, think, feel, and act toward our bodies in terms of size, shape, and general appearance. [ 4 ] BIC is associated with several variables such as weight control, self-esteem, body mass index and depressive symptoms,[ 2 3 5 6 7 ] eating disorders,[ 8 ] short- and long-term maintenance of physical activity,[ 9 ] experiential avoidance and metacognition beliefs,[ 4 ] sociocultural factors,[ 6 ] and mental health. [ 10 ] Body image dissatisfaction is considered as the primary motivation for cosmetic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found a close link between sports activity and the onset of EDs and agree that EDs are more common in female athletes than in non-athletes [20][21][22][23][24][25][26][27][28]. Lots of scienti ic papers address this complex issue.…”
Section: Body Image and Eating Disordersmentioning
confidence: 99%
“…In order to reduce body weight, they may resort to dysfunctional coping styles such as skipping meals, using rubberized clothing to sweat, vomiting, laxatives or diuretics [21,27,32]. A prolonged low-calorie diet that is not adequately monitored can induce an alteration in the relationship between the subject, the food and the perception of one's body and it is an important risk factor for a possible onset of EDs [22,29].…”
Section: Body Image and Eating Disordersmentioning
confidence: 99%